Ion track etching revisited: II. Electronic properties of aged tracks in polymers. Issue 1 (1st February 2018) - Fink, D.; Muñoz Hernández, G.; Cruz, S. A.; Garcia-Arellano, H.; Vacik, J.; Hnatowicz, V.; Kiv, A.; Alfonta, L.
ABSTRACT: We compile here electronic ion track etching effects, such as capacitive-type currents, current spike emission, phase shift, rectification and background currents that eventually emerge upon application of sinusoidal alternating voltages across thin, aged swift heavy ion-irradiated polymer foils during etching. Both capacitive-type currents and current spike emission occur as long as obstacles still prevent a smooth continuous charge carrier passage across the foils. In the case of sufficiently high applied electric fields, these obstacles are overcome by spike emission. These effects vanish upon etchant breakthrough. Subsequent transmitted currents are usually of Ohmic type, but shortly after breakthrough (during the track' core etching) often still exhibit deviations such as strong positive phase shifts. They stem from very slow charge carrier mobility across the etched ion tracks due to retarding trapping/detrapping processes. Upon etching the track's penumbra, one occasionally observes a split-up into two transmitted current components, one with positive and another one with negative phase shifts. Usually, these phase shifts vanish when bulk etching starts. Current rectification upon track etching is a very frequent phenomenon. Rectification uses to inverse when core etching ends and penumbra etching begins. When the latter ends, rectification largely vanishes. Occasionally, some residual rectification remains which we attribute to the aged polymeric bulk itself. Last not least, we still consider background currents which often emerge transiently during track etching. We could assign them clearly to differences in the electrochemical potential of the liquids on both sides of the etched polymer foils. Transient relaxation effects during the track etching cause their eventually chaotic behaviour.